Photosensitive resin laminate and application thereof
Patent Information
- Application Number
- JP2024048472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-01-04
- Filing Date
- 2024-03-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-03-25
AI Technical Summary
【0016】 本願発明の前記の課題、技術的特徴及び利点をより明らかにするために、以下にいくつかの特定の実施態様を参照して本願発明を詳細に説明する。
Smart Images

Figure 2025036041000001 
Figure 2025036041000002 
Figure 2025036041000003
Abstract
Description
[Technical field]
[0001] Priority claim This application claims priority to U.S. Provisional Patent Application No. 63 / 536,189, filed September 1, 2023, and Chinese Patent Application No. 202410010516.8, filed January 4, 2024. The subject matter of these patent applications is incorporated herein by reference in its entirety.
[0002] FIELD OF THEINVENTION The present application provides a photosensitive resin laminate, in particular a photosensitive resin laminate having a large total thickness, and applications of the photosensitive resin laminate. [Background technology]
[0003] Photosensitive resin film is a film that undergoes chemical changes after exposure, and is used in electronics as photoresist film. According to the changes after exposure, photoresist film can be classified into positive photoresist film and negative photoresist film. In positive photoresist film, the exposed part of the photoresist film dissolves during development, leaving the unexposed part of the photoresist film. In negative photoresist film, the unexposed part of the photoresist film dissolves during development, leaving the exposed part of the photoresist film.
[0004] In the printed circuit board (PCB) industry, photoresist films are used in etching or electroplating procedures to form circuit patterns. Due to the increasing complexity and size of electronic components, the printed circuit board industry requires thicker photoresist films with higher depth to width ratios. However, conventional photoresist films often exhibit poor adhesion or contain bubbles or wrinkles, which lead to defects in subsequent etching or electroplating procedures. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above technical problems, the present invention aims to provide a solution to improve the adhesion, storage properties, and operability of photoresist films. Through research, it has been found that these technical problems can be addressed by a photosensitive resin laminate consisting of multiple photosensitive resin layers.
[0006] Therefore, an object of the present invention is to provide a photosensitive resin laminate comprising two or more photosensitive resin layers and containing a second component, When the photosensitive resin laminate is characterized by gas chromatography using added toluene as an internal standard, the retention time of the elution peak of the second component is in the range of 0.55 minutes to 1.30 minutes, the retention time of the added toluene is in the range of 1.32 minutes to 1.65 minutes, and the following formula is satisfied:
number
[0007] In some embodiments of the present invention, the photosensitive resin laminate is dissolved in propylene glycol methyl ether with added toluene as an internal standard to prepare a solution, and the solution is tested under the following conditions to perform gas chromatography: <Conditions> A stainless steel column with a column length of 3 m, an outer diameter of 1 / 8 inch, and a column wall thickness of 0.02 inch is used; a porous polymer stationary phase is used as the packing material; a flow rate of 20 ml / min and a supply pressure of 5 kgf / cm 2of helium is used as the carrier gas; stepwise heating conditions are applied: 80°C for 0.1 min, heating from 80°C to 96°C at a heating rate of 4°C / min, heating from 96°C to 135°C at a heating rate of 10°C / min, and holding at 135°C for 2 min; the injection port temperature is 180°C; the solution injection volume is 3 μl; and a thermal conductivity detector at 200°C is used.
[0008] In some embodiments of the present invention, the two or more photosensitive resin layers each independently have a thickness of 50 μm to 300 μm.
[0009] In some embodiments of the present invention, the photosensitive resin laminate comprises 2 to 4 photosensitive resin layers.
[0010] In some embodiments of the present invention, the two or more photosensitive resin layers are each independently a dry film.
[0011] In some embodiments of the present invention, the two or more photosensitive resin layers each independently contain (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, and (C) a photopolymerization initiator.
[0012] In some embodiments of the present invention, the ethylenically unsaturated compound, component (B), comprises one or more difunctional acrylate compounds.
[0013] In some embodiments of the present invention, the amount of the difunctional acrylate compound based on the weight of the ethylenically unsaturated compound, component (B), is 60% by weight or more.
[0014] Another object of the present invention is to provide a composite laminate comprising the above-mentioned photosensitive resin laminate and a non-photosensitive resin film on at least one surface of the photosensitive resin laminate.
[0015] In some embodiments of the present invention, the non-photosensitive resin film is selected from the group consisting of polyethylene terephthalate film, polyolefin film, and composites thereof.
[0016] In order to make the above objects, technical features and advantages of the present invention more apparent, the present invention will be described in detail below with reference to some specific embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Some specific embodiments of the present invention will now be described in detail, however the present invention may be embodied in various embodiments and should not be limited to the embodiments set forth herein.
[0018] Unless otherwise specifically stated, the terms "a," "the," "the" and the like used in the specification and claims are intended to include both the singular and the plural forms.
[0019] Unless otherwise specified, the terms "first", "second", etc. in the present specification and claims have no special meaning and are used only to distinguish between the elements or components described. These terms are not used to indicate priority.
[0020] Unless further explained, the terms "(meth)acrylic acid", "(meth)acrylate", etc. are intended to cover both embodiments with and without the functional group within the brackets. For example, the term "(meth)acrylic acid" is intended to cover both acrylic acid and methacrylic acid. The term "methyl (meth)acrylate" is intended to cover both methyl acrylate and methyl methacrylate.
[0021] In this specification and claims, weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC) and calculated by comparison with a standard sample. The unit of weight average molecular weight (Mw) is "g / mol".
[0022] The effect of the present invention over the prior art is to provide a thick photosensitive resin laminate having excellent adhesion, storage properties, and handling properties by controlling the gas chromatography properties of the photosensitive resin laminate. The photosensitive resin laminate of the present invention and its application will be described in detail below.
[0023] 1. Photosensitive resin laminate The photosensitive resin laminate of the present invention is composed of two or more photosensitive resin layers and contains a second component. The second component can be contained in the photosensitive resin layer of the photosensitive resin laminate. In some embodiments of the present invention, the photosensitive resin laminate is composed of 2 to 4 photosensitive resin layers, and each photosensitive resin layer contains the second component.
[0024] In some embodiments of the present invention, the photosensitive resin laminate is essentially free of toluene. That is, the amount of toluene based on the total weight of the photosensitive resin laminate is 0.5 wt% or less. For example, the amount of toluene based on the total weight of the photosensitive resin laminate can be 0.5 wt%, 0.45 wt%, 0.4 wt%, 0.35 wt%, 0.3 wt%, 0.25 wt%, 0.2 wt%, 0.15 wt%, 0.1 wt%, 0.05 wt%, or 0.01 wt%. In some embodiments of the present invention, the photosensitive resin laminate is free of toluene.
[0025] The photosensitive resin laminate of the present invention can be used as a positive photoresist film or a negative photoresist film. In some embodiments of the present invention, the photosensitive resin laminate is used as a negative photoresist film. That is, after exposure of the photoresist film, the unexposed part is dissolved in the development process, and the exposed part remains.
[0026] The total thickness of the photosensitive resin laminate of the present invention is in the range of 100 μm to 600 μm. For example, the total thickness of the photosensitive resin laminate of the present invention is 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, It can be 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 520 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, or 600 μm, or between these two values. The thicker the photosensitive resin laminate, the thicker the possible thickness for plating a metal conductive layer when the photosensitive resin laminate is used as a photoresist film. Therefore, the photosensitive resin laminate is particularly suitable for the packaging of 2.5D and 3D integrated circuits, and is useful for patterning before plating a conductive layer.
[0027] 1.1. Gas chromatographic characteristics of photosensitive resin laminate The photosensitive resin laminate of the present invention has specific gas chromatography characteristics. In particular, when the photosensitive resin laminate is characterized by gas chromatography using added toluene as an internal standard, the retention time of the elution peak of the second component is in the range of 0.55 minutes to 1.30 minutes, and the retention time of the added toluene is in the range of 1.32 minutes to 1.65 minutes, satisfying the following formula:
number
[0028] In the above formula, "0.1% to 7.0%" means that the value obtained by calculating the left side of the equation can be in the range of 0.1% to 7.0%. For example, in the above formula, the value obtained by calculating the left side of the equation can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 3.10%, 3.11%, 3.12%, 3.13%, 3.14%, 3.15%, 3.16%, 3.17%, 3.18%, 3.19%, 3.20%, 3.21%, 3.22%, 3.23%, 3.24%, 3.25%, 3.26%, 3.27%, 3.28%, 3.29%, 3.30%, 3.31%, 3.32%, 3.33%, 3.34%, 3.35%, 3.36%, 3.37%, 3.38%, 3.39%, 3.39%, 3.40%, 3.41%, 3.42%, 3.43%, 3.44%, 3.45%, 3.46%, 3.47%, 3.48%, 3.49%, The value may be 6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, or 7.0%, or may fall within a range between any two of these recited values.
[0029] Gas chromatography is performed by dissolving the photopolymer laminate in propylene glycol methyl ether with added toluene as an internal standard to form a solution, and testing the solution under the following conditions: <Conditions> A stainless steel column with a column length of 3 m, an outer diameter of 1 / 8 inch, and a column wall thickness of 0.02 inch is used; a porous polymer stationary phase is used as the packing material; a flow rate of 20 ml / min and a supply pressure of 5 kgf / cm 2 of helium is used as the carrier gas; stepwise heating conditions are applied: 80°C for 0.1 min, heating from 80°C to 96°C at a heating rate of 4°C / min, heating from 96°C to 135°C at a heating rate of 10°C / min, and holding at 135°C for 2 min; the injection port temperature is 180°C; the solution injection volume is 3 μl; and a thermal conductivity detector at 200°C is used. In the above test conditions, the porous polymer stationary phase can be a column with model number: CRS BX-10 (Heng Yi Enterprise Company).
[0030] The weight of the photosensitive resin laminate used in gas chromatography can be in the range of 11g to 19.5g. The amount of added toluene used in gas chromatography can be in the range of 0.45g to 0.55g. For example, the weight of the photosensitive resin laminate can be 11g, 11.5g, 12g, 12.5g, 13g, 13.5g, 14g, 14.5g, 15g, 15.5g, 16g, 16.5g, 17g, 17.5g, 18g, 18.5g, or 19g, or within the range between these two values. The amount of added toluene can be 0.45g, 0.46g, 0.47g, 0.48g, 0.49g, 0.50g, 0.51g, 0.52g, 0.53g, 0.54g, or 0.55g, or within the range between these two values. In gas chromatography, the weight of the photosensitive resin laminate used is preferably 25 to 35 times the amount of added toluene, thereby achieving a better signal-to-noise ratio. In some embodiments of the present invention, the weight of the photosensitive resin laminate used in gas chromatography is 15 g, and the amount of added toluene is in the range of 0.50 g to 0.53 g.
[0031] The weight of propylene glycol methyl ether used in gas chromatography can be in the range of 55g to 65g. For example, the weight of propylene glycol methyl ether used in gas chromatography can be 55g, 56g, 57g, 58g, 59g, 60g, 61g, 62g, 63g, 64g, or 65g, or within the range between these two values. In gas chromatography, the retention time of propylene glycol methyl ether is later than the retention time of added toluene. In some embodiments of the present invention, the elution peak of propylene glycol methyl ether corresponds to a retention time of 1.9 minutes to 6.9 minutes.
[0032] 1.2. Photosensitive resin layer The photosensitive resin laminate of the present invention may be composed of two or more photosensitive resin layers. For example, the photosensitive resin laminate of the present invention may be composed of two, three or four photosensitive resin layers, but the present invention is not limited thereto. Each photosensitive resin layer may independently have a thickness in the range of 50 μm to 300 μm. For example, the photosensitive resin layers can each independently have a thickness of 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, or 300 μm, or a thickness within a range between two of these recited values.
[0033] In some embodiments of the present invention, the photosensitive resin layer is a dry film. This means that the photosensitive resin film has a low solvent content. The term "low solvent content" means that the amount of solvent based on the total weight of the photosensitive resin film is 0.1% by weight to 8% by weight, more particularly 0.1% by weight to 7% by weight. In contrast to ink-like and liquid-like wet films, dry films are less likely to flow or deform due to their low solvent content, and can be attached to a substrate without the need for additional processes such as coating or drying. Therefore, dry films are easier to control and have excellent operability.
[0034] On the premise that the photosensitive resin laminate satisfies the above-mentioned chromatographic properties, the composition of the two or more photosensitive resin layers forming the photosensitive resin laminate can be adjusted as necessary. The compositions of the two or more different photosensitive resin layers can be the same or different. In some embodiments of the present invention, the photosensitive resin layers each independently contain (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, (C) a photopolymerization initiator, a second component, and any additives.
[0035] 1.2.1.(A) Alkali-soluble polymer Examples of alkali-soluble polymers include, but are not limited to, carboxy-containing acrylic acid-based polymers, carboxy-containing vinyl aromatic polymers, carboxy-containing norbornene-based polymers, carboxy-containing epoxy-based polymers, carboxy-containing amide-based polymers, carboxy-containing amide epoxy-based polymers, carboxy-containing alkyd-based polymers, and carboxy-containing phenol-based polymers.The above-mentioned alkali-soluble polymers can be used alone or in combination.In some embodiments of the present invention, the alkali-soluble polymer is a carboxy-containing acrylic acid-based polymer.
[0036] For example, an alkali-soluble polymer can be obtained by polymerizing one or more carboxy-containing polymerizable monomers, or by copolymerizing one or more carboxy-containing polymerizable monomers with other polymerizable monomers that do not contain carboxyl. Thus, the alkali-soluble polymer can contain one or more repeat units derived from the carboxy-containing polymerizable monomer, or one or more repeat units derived from the carboxy-containing polymerizable monomer and one or more repeat units derived from the other polymerizable monomer.
[0037] In some embodiments of the present invention, the alkali-soluble polymer has at least one repeat unit derived from a first polymerizable monomer and at least one repeat unit derived from a second polymerizable monomer, and the first polymerizable polymer contains carboxy. Examples of the first polymerizable monomer include, but are not limited to, (meth)acrylic acid, α-bromo(meth)acrylic acid, α-chloro(meth)acrylic acid, β-phthalimide(meth)acrylic acid, β-styryl(meth)acrylic acid, propiolic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, and maleic acid. The second polymerizable monomer does not contain carboxy. Examples of the second polymerizable monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tert-butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-methylcyclopentyl (meth)acrylate, 1-methylcyclohexyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, 2-butyl-2-adamantyl (meth)acrylate, tetrahydrofurfuryl methyl (meth)acrylate-based compounds such as (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, glycidyl methacrylate, 2,2,2-trifluoroethyl (meth)acrylate, and 2,2,3,3-tetrafluoropropyl (meth)acrylate; (meth)acrylonitrile; vinyl ester-based compounds such as vinyl acetate and vinyl n-butylate; vinyl aromatic-based compounds such as styrene, vinyl naphthalene, 3-acetoxystyrene, 4-acetoxystyrene, vinyl toluene, and α-methylstyrene; norbornene; acrylamide; maleate-based compounds such as monomethyl maleate, monoethyl maleate, and monoisopropyl maleate; and derivatives of the above polymerizable monomers, but are not limited to these.The first polymerizable monomer and the second polymerizable monomer may be used alone or in combination.
[0038] In a preferred embodiment of the present invention, an alkali-soluble polymer can be obtained by copolymerizing (meth)acrylic acid with one or more (meth)acrylate compounds. Thus, the alkali-soluble polymer contains repeating units derived from (meth)acrylic acid and repeating units derived from (meth)acrylate compounds. The weight ratio of (meth)acrylic acid to (meth)acrylate compounds can be 1:20 to 1:1, more particularly 1:6 to 1:4. For example, the weight ratio of (meth)acrylic acid to (meth)acrylate compounds can be 1:20, 1:19, 1:18, 1:17, 1:16, 1:15, 1:14, 1:13, 1:12, 1:11, 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, or 1:1, or within a range between any two of these listed values.
[0039] The weight average molecular weight (Mw) of the alkyl-soluble polymer can be 10,000 to 180,000, preferably 40,000 to 80,000. For example, the weight average molecular weight of the alkyl-soluble polymer can be 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000, 95,000, 10 ... In one embodiment, the amount of the at least one ion exchange rate can be 0.05,000, 110,000, 115,000, 120,000, 125,000, 130,000, 135,000, 140,000, 145,000, 150,000, 155,000, 160,000, 165,000, 170,000, 175,000, or 180,000, or within a range between any two of these recited values.
[0040] The amount of the alkyl-soluble polymer based on the weight of the photosensitive resin layer in which it is present can be from 20% to 85% by weight, particularly from 40% to 80% by weight, and more particularly from 50% to 75% by weight. For example, the amount of alkyl-soluble polymer based on the weight of the photosensitive resin layer in which it is present can be 20 wt%, 22.5 wt%, 25 wt%, 27.5 wt%, 30 wt%, 32.5 wt%, 35 wt%, 37.5 wt%, 40 wt%, 42.5 wt%, 45 wt%, 47.5 wt%, 50 wt%, 52.5 wt%, 55 wt%, 57.5 wt%, 60 wt%, 62.5 wt%, 65 wt%, 67.5 wt%, 70 wt%, 72.5 wt%, 75 wt%, 77.5 wt%, 80 wt%, 82.5 wt%, or 85 wt%, or within a range between any two of these recited values.
[0041] 1.2.2.(B) Ethylenically unsaturated compound components The ethylenically unsaturated compound refers to a compound having at least one reactive ethylenic functional group, and is preferably a difunctional compound having two reactive ethylenic functional groups. In some embodiments of the present invention, the ethylenically unsaturated compound component includes a monofunctional or polyfunctional acrylate compound, and preferably a difunctional acrylate compound. Examples of acrylate-based compounds include, but are not limited to, ethoxylated bisphenol-A dimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol-A diacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, polypropylene glycol diacrylate, tris((meth)acryloxyisocyanate)hexamethylene isocyanurate, ethoxylated urethane di(meth)acrylate, propoxylated urethane di(meth)acrylate, ethoxylated / propoxylated urethane di(meth)acrylate, ethoxylated tris(methacryloxyisocyanate)hexamethylene isocyanurate, acrylated tris(methacryloxyisocyanate)hexamethylene isocyanurate, and ethoxylated / propoxylated tris(methacryloxyisocyanate)hexamethylene isocyanurate. Furthermore, in each photosensitive resin layer, the amount of the difunctional acrylate compound based on the weight of the ethylenically unsaturated compound component in each photosensitive resin layer is preferably 60% by weight or more.For example, the amount of the difunctional acrylate compound based on the weight of the ethylenically unsaturated compound component in each photosensitive resin layer can be 60% by weight, 62.5% by weight, 65% by weight, 67.5% by weight, 70% by weight, 72.5% by weight, 75% by weight, 77.5% by weight, 80% by weight, 82.5% by weight, 85% by weight, 87.5% by weight, 90% by weight, 92.5% by weight, 95% by weight, 97.5% by weight, or 100% by weight, or within the range between these two values.
[0042] In some embodiments of the present invention, the ethylenically unsaturated compound component includes at least one of ethoxylated bisphenol-A dimethacrylate and trimethylolpropane triacrylate.
[0043] The amount of the ethylenically unsaturated compound component based on the weight of the photosensitive resin layer in which the ethylenically unsaturated compound component is present can be in the range of 5% by weight to 70% by weight, particularly 15% by weight to 50% by weight, and more particularly 20% by weight to 45% by weight. For example, the amount of the ethylenically unsaturated compound component based on the weight of the photosensitive resin layer in which the ethylenically unsaturated compound component is present can be 5 wt%, 7.5 wt%, 10 wt%, 12.5 wt%, 15 wt%, 17.5 wt%, 20 wt%, 22.5 wt%, 25 wt%, 27.5 wt%, 30 wt%, 32.5 wt%, 35 wt%, 37.5 wt%, 40 wt%, 42.5 wt%, 45 wt%, 47.5 wt%, 50 wt%, 52.5 wt%, 55 wt%, 57.5 wt%, 60 wt%, 62.5 wt%, 65 wt%, 67.5 wt%, or 70 wt%, or within a range between any two of these recited values.
[0044] 1.2.3.(C) Photoinitiator A photopolymerization initiator refers to a substance that can initiate a polymerization reaction in the presence of light. The type of photopolymerization initiator is not particularly limited. Examples of photopolymerization initiators include, but are not limited to, imidazole-based compounds, ketone-based compounds, quinone-based compounds, benzoin-based or benzoin ether-based compounds, polyhalogenated compounds, triazine-based compounds, organic peroxide compounds, onium compounds, and other commonly known photopolymerization initiators. The photopolymerization initiators can be used alone or in combination.
[0045] Examples of imidazole compounds include, but are not limited to, 2,4,5-triarylimidazole dimers such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer.
[0046] Examples of ketone compounds include, but are not limited to, benzophenone, 4,4-bis(dimethylamino)benzophenone, 4-methoxy-4'-dimethylaminobenzophenone, 4,4'-dimethoxybenzophenone, 4-dimethylaminobenzophenone, 4-dimethylaminoacetophenone, xanthone, thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, acridone, α-hydroxyacetophenone, α-aminoacetophenone, α-hydroxycycloalkylphenone, and dialkylacetophenone.
[0047] Examples of quinone compounds include, but are not limited to, camphorquinone, benzanthraquinone, 2-tert-butylanthraquinone, and 2-methylanthraquinone.
[0048] Examples of benzoin or benzoin ether compounds include, but are not limited to, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, and benzoin phenyl ether.
[0049] Examples of polyhalogenated compounds include, but are not limited to, carbon tetrabromide, phenyl tribromomethyl sulfone, and phenyl trichloromethyl ketone.
[0050] Examples of triazine compounds include, but are not limited to, 2,4,6-tris(trichloromethyl)-s-triazine, 2-methoxy-4,6-bis(trichloromethyl)-s-triazine, 2-amino-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methoxystyryl)-4,6-bis(trichloromethyl)-s-triazine.
[0051] Examples of organic peroxide compounds include, but are not limited to, methyl ethyl ketone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, benzoyl peroxide, di-tert-butyl isophthalate peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butyl peroxybenzoate, a,a'-bis(tert-butylperoxyisopropyl)benzene, dicumyl peroxide, and 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone.
[0052] Examples of onium compounds include, but are not limited to, diaryliodonium or triarylsulfonium salts obtained by combining diphenyliodonium, 4,4'-dichlorodiphenyliodonium, 4,4'-dimethoxydiphenyliodonium, 4,4'-di-tert-butyldiphenyliodonium, 4-methyl-4'-isopropyldiphenyliodonium, or 3,3'-dinitrodiphenyliodonium with chloride, bromide, tetrafluoroborate, hexafluorophosphate, hexafluoroarsenate, hexafluoroantimonate, tetrakis(pentafluorophenyl)borate, or trifluoromethanesulfonic acid.
[0053] Other common well-known examples of photoinitiators include, but are not limited to, fluorine, bisacylphosphine oxides, azinium compounds, organoboron compounds, phenylglyoxylates, and titanocenes.
[0054] In some embodiments of the present invention, the photoinitiator is an imidazole-based compound or a ketone-based compound.
[0055] The amount of photopolymerization initiator based on the weight of the photosensitive resin layer in which it is present can be in the range of 0.1% to 15% by weight, particularly 0.5% to 10% by weight, and more particularly 1% to 5% by weight. For example, the amount of photoinitiator based on the weight of the photosensitive resin layer in which it is present can be 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt%, or 15 wt%, or within a range between any two of these recited values.
[0056] 1.2.4. Second Component In the present invention, the second component refers to a component that contributes to an elution peak having a retention time in the range of 0.55 minutes to 1.30 minutes when the photosensitive resin laminate is characterized by gas chromatography using added toluene as an internal standard. The second component can be present in at least one photosensitive resin layer, and preferably in all photosensitive resin layers forming the photosensitive resin laminate.
[0057] In some embodiments of the present invention, the second component of the photosensitive resin layer can be at least one of an inactive ester, ketone, ether, or alcohol, each of which independently has a boiling point in the range of 55° C. to 90° C. The term "inactive ester, ketone, ether, or alcohol" refers to an ester, ketone, ether, or alcohol that is miscible with, but does not react with, the other components of the photosensitive resin layer. For example, the second component can include at least one of methyl acetate, ethyl acetate, acetone, methyl ethyl ketone, methanol, ethanol, and isopropanol.
[0058] 1.2.5. Optional Additives On the premise that the photosensitive resin laminate satisfies the above-mentioned chromatographic properties, the two or more photosensitive resin layers forming the photosensitive resin laminate can further contain additives to improve the properties of the photosensitive resin layers. Examples of additives include, but are not limited to, solvents, light absorbers, dyes, pigments, radical initiators, and surfactants. The additives can be used alone or in combination.
[0059] 1.3. Preparation of photosensitive resin laminate The method for preparing the photosensitive resin laminate of the present invention is not particularly limited. A person skilled in the art can prepare a photosensitive resin laminate based on the description of the specification of the present application, particularly based on the specific description of the examples. For example, a method for preparing a photosensitive resin laminate containing the above-mentioned exemplified components includes uniformly mixing each component of the photosensitive resin film containing (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, (C) a photopolymerization initiator, a second component, and any additives with a mixer. Subsequently, the mixture is dissolved or dispersed in a solvent to form a photosensitive solution, and the photosensitive solution is coated on a substrate. The coated photosensitive solution is dried to obtain a photosensitive resin layer. The composition of the photosensitive solution can be changed as desired, and these steps can be repeated to obtain further photosensitive resin layers. Finally, the obtained photosensitive resin layers can be stacked, pressed, or bonded together to obtain a photosensitive resin laminate.
[0060] The coating method of the photosensitive solution is not particularly limited and can be any existing coating method in the art.Examples of the existing coating method include, but are not limited to, gravure coating, reverse roll coating, die coating, air scraper coating, scraper coating, rod coating, scraper rod coating, curtain coating, knife coating, transfer roll coating, extrusion press coating, dip coating, kiss coating, spray coating, calendar coating, and extrusion coating.In some embodiments of the present invention, the coating method of the photosensitive solution is preferably scraper coating, rod coating, scraper rod coating, or die coating.
[0061] In some embodiments of the present invention, in order to dry the photosensitive resin layer to an appropriate extent, the coated photosensitive solution can be heated at a temperature in the range of 70°C to 200°C for 1 to 40 minutes, preferably at 100°C to 180°C for 1 to 40 minutes.
[0062] The detailed preparation method of the photosensitive resin laminate will be described in the following Examples.
[0063] 2. Application of photosensitive resin laminate The photosensitive resin laminate of the present invention can be used as a photoresist film and is applied in various electronic engineering fields. Generally, before the use of the photoresist film, both surfaces of the photoresist film can be covered with a protective film to provide protection and support. This facilitates the storage of the photoresist film and protects the photoresist film from contamination or damage by foreign substances. Similarly, a protective film can be provided on both sides of the photosensitive resin laminate. The protective film is preferably a non-photosensitive resin film.
[0064] Therefore, the present invention also provides a composite film comprising the above-mentioned photosensitive resin laminate and a non-photosensitive resin film on at least one surface of the photosensitive resin laminate. In a preferred embodiment of the present invention, the non-photosensitive resin film is provided on both surfaces of the photosensitive resin laminate, and the materials of the non-photosensitive resin films on two different surfaces of the photosensitive resin laminate can be the same or different.
[0065] The type of non-photosensitive resin film is not particularly limited and can be any conventional material known in the art. For example, the non-photosensitive resin film that can be used in the present invention can be selected from the group consisting of polyethylene terephthalate film (PET film), polyolefin film, and composites thereof. Examples of polyolefin films include, but are not limited to, polyethylene film (PE film) and polypropylene film (PP film), such as polypropylene stretched film. The composite can be a composite of polyethylene terephthalate film and polyolefin film, or a composite of different polyolefin films. In a preferred embodiment of the present invention, the composite laminate includes a PET film on one surface of the photosensitive resin laminate and a PE film on the other surface of the photosensitive resin laminate.
[0066] The method for preparing the composite laminate of the present invention is not particularly limited and can be any method known in the art. A person skilled in the art can prepare the composite laminate based on the description of the present specification. For example, the composite laminate can be prepared by stacking non-photosensitive resin films on both surfaces of a photosensitive resin laminate to provide a stacked object, and pressing the stacked object to obtain a composite laminate. Alternatively, the composite film can be prepared by forming a photosensitive resin layer between two non-photosensitive resin films by coating or extrusion. The non-photosensitive resin film on the surface of the photosensitive resin layer that is to be in contact with the other photosensitive resin layer can be peeled off, followed by stacking and pressing to obtain a composite laminate.
[0067] Detailed methods for preparing the composite laminates are described in the Examples below. EXAMPLES
[0068] 3. Working Example Test Method [Number of layers of photosensitive resin laminate] The prepared composite laminate was cut into 10 mm x 15 mm pieces along the transverse direction (TD) and machine direction (MD) at random positions. The PE and PET films were removed from both surfaces of the photopolymer laminate. The photopolymer laminate was placed with a jig on the analysis platform of a microscope (model number: Olympus MX51). The position of the sample was adjusted to ensure that the cut surface of the sample was perpendicular to the viewing angle of the objective lens. The cut surface was observed under a fluorescent filter, a 10x objective lens (model number: MPlanFL N) and a 10x eye lens. When clear interfaces were observed between the layers, it was indicated that the sample had a laminated structure. Each identified interface was counted to determine the number of layers of the photopolymer laminate (= "number of identified interfaces + 1").
[0069] [Gas chromatography of photosensitive resin laminate] The PE film and PET film of the composite laminate were removed from both surfaces of the photosensitive resin laminate. The prepared composite laminate was cut into 15 g samples along the transverse direction (TD) and machine direction (MD) at arbitrary positions. The obtained photosensitive resin laminate sample was dissolved in 60 g of propylene glycol methyl ether, and 0.50 g to 0.53 g of toluene was added as an internal standard to prepare a solution. Gas chromatography was performed under the following conditions. <Conditions> A stainless steel column with a column length of 3 m, an outer diameter of 1 / 8 inch, and a column wall thickness of 0.02 inch is used; CRS BX-10 (Heng Yi Enterprise Company) is used as the packing material; the flow rate is 20 ml / min and the supply pressure is 5 kgf / cm 2of helium is used as the carrier gas; stepwise heating conditions are applied: 80°C for 0.1 min, heating from 80°C to 96°C at a heating rate of 4°C / min, heating from 96°C to 135°C at a heating rate of 10°C / min, and holding at 135°C for 2 min; the injection port temperature is 180°C; the solution injection volume is 3 μl; and a thermal conductivity detector at 200°C is used. The analysis was performed using the analytical software Qchrom V1.2 from Scientific Information Service Company. Calculations were performed according to the following formula, and the obtained values were recorded as "Gas Chromatography Calculation Results."
number
[0070] [Air bubble analysis of photosensitive resin laminate] The prepared composite laminate was cut at any position into a size of 10 mm x 15 mm along the transverse direction (TD) and machine direction (MD). The PE film was removed. The obtained photopolymer laminate was placed on a transparent glass along with the PET film thereon with the surface of the photopolymer laminate facing the transparent glass. This assembly was placed in a laminator and laminated under the following conditions: lamination speed 0.5 m / min, lamination pressure 3.0 kg / cm. 2 , and pressed at a lamination temperature of 25°C. The PET film was then removed. The resulting photosensitive resin laminate was placed on a black flat substrate along with the glass, and exposed to light with an exposure energy of 100 mJ / cm 2 The photopolymer laminate was exposed to light until it reached a thickness of 10 mm. A 1% aqueous Na2CO3 solution at 30°C was used as the developer, and the photopolymer laminate was immersed in the developer along with the glass for 10 minutes. After development, the photopolymer laminate was removed along with the glass, washed with pure water for 10 seconds, and air-dried. An arbitrary area of 5 cm x 5 cm in the center of the glass was selected and observed. This area was divided into subareas of 5 mm x 5 mm, and the subareas were successively observed for bubbles under a microscope with a 10x eyepiece. The number of bubbles whose major axis was longer than 0.5 times the total thickness of the photopolymer laminate was recorded.
[0071] [Wrinkle test for photosensitive resin laminate] The prepared composite laminate was wound into a slit roll having a length of 30 m and a width of 300 mm, and left at a temperature of 23°C to 27°C for 16 hours. Then, a composite laminate having a length of 5 m was pulled out from the slit roll, and the PE protective film of the composite laminate was peeled off. Then, the surface of the photosensitive resin laminate was visually observed. The number of wrinkles having a length of 10 mm or more and a width of 1 mm or more present within a range of 3 m to 5 m of the photosensitive resin laminate was recorded. If no wrinkles having a length of 10 mm or more and a width of 1 mm or more were observed, it indicates that the photosensitive resin laminate has excellent storage properties and operability.
[0072] [100-grid adhesion test of thermally stimulated resin laminate] According to ASTM D3359, the 100-grid adhesion test of the photosensitive resin laminate was carried out in the following manner. A copper-clad laminate (model: CCP-308, Chang Chun Plastics Co., Ltd.) with a thickness of 1.6 mm was prepared. The copper foil of the copper-clad laminate had a thickness of 35 μm. The copper-clad laminate was subjected to brush polishing using a #320 nonwoven brush wheel and a #600 nonwoven brush wheel. The temperature of the surface of the copper foil of the copper-clad laminate was adjusted to 50° C. The PE film on the surface of the prepared composite laminate was peeled off. The photosensitive resin laminate along with the PET film was stacked on the surface of the copper foil so that the photosensitive resin laminate faced the surface of the copper foil of the copper-clad laminate. The stack was laminated with a laminator to provide a sample. The lamination temperature was 80° C. and the lamination pressure was 3.0 kg / cm. 2 The lamination speed was 2.0 mm / min. The PET film on the sample was peeled off, and the photopolymer laminate of the sample was cut into 100 grids of 10×10 squares with a spacing of 1 mm to 1.2 mm using a knife. A transparent tape manufactured by 3M Company (model: 3M Transparent 600) was adhered to the surface of the photopolymer laminate of the grid. At an angle of 45° with the substrate, the tape was quickly peeled off. The number of grids from which the photopolymer laminate was peeled off relative to all grids was calculated and recorded as a percentage. A lower percentage indicates that the photopolymer laminate was better adhered to the copper clad laminate.
[0073] 3.2. Preparation method 3.2.1. Synthesis of alkali-soluble polymers According to the following synthesis examples 1 to 7, carboxy-containing acrylic acid polymers were prepared as alkali-soluble polymers.
[0074] [Synthesis Example 1] As copolymerization monomers, 15 g of methacrylic acid, 60 g of methyl methacrylate, and 25 g of butyl acrylate were mixed with 1.8 g of azobisisoheptylnitrile to prepare solution a1. Separately, 0.7 g of azobisisoheptylnitrile was dissolved in 20 g of ethyl acetate to prepare solution b1.
[0075] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared. 80g of ethyl acetate was added to the flask and heated to 70°C. Solution a1 was added dropwise to the flask at a constant rate over 3 hours, the solution in the flask was maintained at a temperature of 70°C and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70°C, solution b1 was added dropwise to the flask at a constant rate over 0.5 hours, the solution in the flask was maintained at a temperature of 70°C and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90°C and stirred for 5 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer A (hereinafter referred to as polymer A) having a weight average molecular weight of 55,000 and a solid content of 50% by weight.
[0076] [Synthesis Example 2] As copolymerization monomers, 15 g of methacrylic acid, 65 g of methyl methacrylate, and 20 g of butyl acrylate were mixed with 0.8 g of azobisisoheptylnitrile to prepare solution a2. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in 20 g of methyl acetate to prepare solution b2.
[0077] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and 102.2 g of methyl acetate was added to the flask and heated to 70 ° C. Solution a2 was added dropwise to the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70 ° C., solution b2 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90 ° C. and stirred for 5 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer B (hereinafter referred to as polymer B) having a weight average molecular weight of 65,000 and a solid content of 45 wt%.
[0078] [Synthesis Example 3] As copolymerization monomers, 20 g of methacrylic acid, 40 g of methyl methacrylate, and 40 g of 2-ethylhexyl acrylate were mixed with 1.2 g of azobisisoheptylnitrile to prepare solution a3. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in 20 g of acetone to prepare solution b3.
[0079] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and 80g of acetone was added to the flask and heated to 70°C. Solution a3 was dripped into the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70°C and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70°C, solution b3 was dripped into the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70°C and stirred for 6 hours. Thereafter, the solution in the flask was heated to 90°C and stirred for 4 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer C (hereinafter referred to as polymer C) having a weight average molecular weight of 55,000 and a solid content of 50% by weight.
[0080] [Synthesis Example 4] As copolymerization monomers, 20 g of methacrylic acid, 60 g of methyl methacrylate, and 20 g of butyl acrylate were mixed with 1 g of azobisisoheptylnitrile to prepare solution a4. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in 20 g of methyl ethyl ketone to prepare solution b4.
[0081] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and 80 g of methyl ethyl ketone was added to the flask and heated to 70 ° C. Solution a4 was added dropwise to the flask at a constant rate over 4 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70 ° C., solution b4 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90 ° C. and stirred for 5 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer D (hereinafter referred to as polymer D) having a weight average molecular weight of 50,000 and a solid content of 50 wt%.
[0082] [Synthesis Example 5] As copolymerization monomers, 20 g of methacrylic acid, 60 g of methyl methacrylate, and 20 g of butyl acrylate were mixed with 1 g of azobisisoheptylnitrile to prepare solution a5. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in a mixed solvent of 10 g of propylene glycol methyl ether (PGME) and 10 g of ethyl acetate to prepare solution b5.
[0083] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and a mixed solvent of 40g of propylene glycol methyl ether and 40g of ethyl acetate was added to the flask and heated to 70°C. Solution a5 was dripped into the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70°C and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70°C, solution b5 was dripped into the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70°C and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90°C and stirred for 5 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer E (hereinafter referred to as polymer E) having a weight average molecular weight of 50,000 and a solid content of 50% by weight.
[0084] [Synthesis Example 6] As copolymerization monomers, 15 g of acrylic acid, 65 g of methyl methacrylate, and 20 g of hydroxyethyl methacrylate were mixed with 1 g of azobisisoheptylnitrile to prepare solution a6. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in a mixed solvent of 4 g of ethanol and 16 g of ethyl acetate to prepare solution b6.
[0085] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and a mixed solvent of 16 g of ethanol and 64 g of ethyl acetate was added to the flask and heated to 70 ° C. Solution a6 was added dropwise to the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70 ° C., solution b6 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90 ° C. and stirred for 5 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer F (hereinafter referred to as polymer F) having a weight average molecular weight of 50,000 and a solid content of 50 wt%.
[0086] [Synthesis Example 7] As copolymerization monomers, 20 g of methacrylic acid, 45 g of methyl methacrylate, and 35 g of 2-ethylhexyl acrylate were mixed with 1.9 g of azobisisoheptylnitrile to prepare solution a7. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in a mixed solvent of 2 g of methanol and 18 g of methyl acetate to prepare solution b7.
[0087] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and a mixed solvent of 8 g of methanol and 72 g of methyl acetate was added to the flask and heated to 70 ° C. Solution a7 was added dropwise to the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 2 hours. While continuously maintaining the solution in the flask at a temperature of 70 ° C., solution b7 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90 ° C. and stirred for 5 hours to complete the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer G (hereinafter referred to as polymer G) having a weight average molecular weight of 45,000 and a solid content of 50 wt%.
[0088] 3.2.2. Preparation of photosensitive solution Information regarding the raw materials used in the preparation of the following photosensitive solutions is provided in Table 1 below.
[0089] [Table 1]
[0090] According to the components and ratios shown in Table 2, photopolymerization initiators, additives, and THF solvent were mixed and stirred for 30 minutes to obtain mixed solutions. Then, the components of the carboxy-containing acrylic acid-based polymer and ethylenically unsaturated compound prepared in each synthesis example were added to the mixed solution and stirred for 1 hour to obtain photosensitive solutions A to H.
[0091] [Table 2]
[0092] 3.2.3. Preparation of photosensitive resin laminate According to Tables 3-1 to 3-3, the photosensitive resin laminates of Examples E1 to E12 and Comparative Examples CE1 to CE15 were prepared to the desired thickness. Specifically, the obtained photosensitive solution was coated on a PET film using a Kodaira wire-wound rod. The coated photosensitive solution was dried in an oven to form a photosensitive resin layer on the PET film. Then, a PE film was stacked on the surface of the photosensitive resin layer that was not in contact with the PET film to obtain photosensitive resin layers 1, 2, 3, and 4 in which both surfaces were coated.
[0093] The PE film was removed from the photosensitive resin layer 1, and the PET film was removed from the photosensitive resin layer 2. The photosensitive resin layer 1 and the photosensitive resin layer 2 were pressed together at the surfaces of the photosensitive resin layers facing each other, resulting in a photosensitive resin laminate including the photosensitive resin layer 1 and the photosensitive resin layer 2.
[0094] The PE film was removed from the photosensitive resin layer 1, and the PET film was removed from the photosensitive resin layer 2. The photosensitive resin layer 1 and the photosensitive resin layer 2 were pressed together at the surfaces of the photosensitive resin layers facing each other. Then, the PE film was removed from the photosensitive resin layer 2, and the PET film was removed from the photosensitive resin layer 3. The photosensitive resin layer 3 was bonded to the surface of the photosensitive resin layer 2 that was not bonded to the photosensitive resin layer 1, and they were pressed together, resulting in a photosensitive resin laminate including the photosensitive resin layer 1, the photosensitive resin layer 2, and the photosensitive resin layer 3.
[0095] The PE film was removed from the photosensitive resin layer 1, and the PET film was removed from the photosensitive resin layer 2. The photosensitive resin layer 1 and the photosensitive resin layer 2 were pressed together at the surfaces of the photosensitive resin layers facing each other. Then, the PE film was removed from the photosensitive resin layer 2, and the PET film was removed from the photosensitive resin layer 3. The photosensitive resin layer 3 was bonded to the surface facing the surface of the photosensitive resin layer 2 that is not bonded to the photosensitive resin layer 1. Furthermore, the PE film was removed from the photosensitive resin layer 3, and the PET film was removed from the photosensitive resin layer 4. The photosensitive resin layer 4 was bonded to the surface facing the surface of the photosensitive resin layer 3 that is not bonded to the photosensitive resin layer 2, and pressed. As a result, a photosensitive resin laminate including the photosensitive resin layer 1, the photosensitive resin layer 2, the photosensitive resin layer 3, and the photosensitive resin layer 4 was obtained.
[0096] [Table 3-1]
[0097] [Table 3-2]
[0098] [Table 3-3]
[0099] 3.3. Testing of photosensitive resin laminates According to the above-mentioned test methods, the properties of the photosensitive resin laminate or the photosensitive resin layer of Examples E1 to E12 and Comparative Examples CE1 to CE15 were tested, including the number of layers of the photosensitive resin laminate, the calculation results of gas chromatography, air bubbles, wrinkles, and 100 grid adhesion properties. The results are shown in Tables 4-1 to 4-3.
[0100] [Table 4-1]
[0101] [Table 4-2]
[0102] [Table 4-3]
[0103] As shown in Tables 4-1 to 4-3, the photosensitive resin laminate of the present invention does not contain air bubbles as defects and does not show wrinkles. This indicates that the photosensitive resin laminate has good handling and storage properties. In addition, the photosensitive resin laminates of Examples E1 to E12 show low peel percentages (<5%) in the 100-grid adhesion test. This indicates good adhesion to copper-clad laminates.
[0104] In contrast, the photosensitive resin laminates of Comparative Examples CE1 to CE10 and CE15 show defects of air bubbles and wrinkles. In addition, these photosensitive resin laminates show poor operability and storage properties because the calculation results of gas chromatography are higher than the specific range (higher than 7.0%). The photosensitive resin laminates of Comparative Examples CE11 to CE13 show defects of air bubbles. In addition, these photosensitive resin laminates show poor adhesion because the calculation results of gas chromatography are lower than the specific range (lower than 0.1%). In particular, Comparative Example CE13 has a photosensitive resin laminate structure, but the calculation results of gas chromatography are lower than the specific range, so it still cannot achieve the effects of the present invention. Comparative Example CE15 has a photosensitive resin laminate structure and a thickness of 600 μm, but the calculation results of gas chromatography exceed the specific range, so it still cannot achieve the effects of the present invention. This emphasizes the importance of the technical features of gas chromatography specified in the present invention.
[0105] On the other hand, Comparative Example CE14 shows that even if the technical features of the gas chromatography of the present invention are satisfied, if the photosensitive resin film does not have a laminate structure, defects such as air bubbles and wrinkles will still occur, which emphasizes the importance of having a photosensitive resin laminate structure and at the same time satisfying the technical features of the gas chromatography specified in the present invention.
[0106] Furthermore, comparison of Example E4 and Comparative Example CE4, Example E2 and Comparative Example CE5, Example E7 and Comparative Example CE6, and Example E11 and Comparative Example CE9 shows that the comparative examples that do not have two or more photosensitive resin layers cannot satisfy the above formula even if they have an ideal total thickness, resulting in the existence of a large number of bubbles and wrinkles. This highlights the importance of the technical feature of having a photosensitive resin laminate structure.
[0107] The above embodiments explain the principles and effects of the present invention and demonstrate its inventive features. Those skilled in the art can make various modifications and replacements based on the disclosure and suggestions of the invention described. Therefore, the protection scope of the present invention is defined in the appended claims.
Claims
1. A photosensitive resin laminate comprising two or more photosensitive resin layers and containing a second component, When the photosensitive resin laminate is characterized by gas chromatography using added toluene as an internal standard, the retention time of the elution peak of the second component is in the range of 0.55 minutes to 1.30 minutes, the retention time of the added toluene is in the range of 1.32 minutes to 1.65 minutes, and the following formula is satisfied: [0010] (wherein the amount of toluene added and the weight of the photosensitive resin laminate are expressed in grams (g).) The photosensitive resin laminate has a total thickness of 100 μm to 600 μm.
2. 2. The photosensitive resin laminate according to claim 1, wherein gas chromatography is performed by dissolving the photosensitive resin laminate in propylene glycol methyl ether with added toluene as an internal standard to prepare a solution, and testing the solution under the following conditions: <Conditions> A stainless steel column with a column length of 3 m, an outer diameter of 1 / 8 inch, and a column wall thickness of 0.02 inch is used; a porous polymer stationary phase is used as the packing material; a flow rate of 20 ml / min and a supply pressure of 5 kgf / cm 2 of helium as the carrier gas; stepwise heating conditions are applied: 80°C for 0.1 min, heating from 80°C to 96°C at a heating rate of 4°C / min, heating from 96°C to 135°C at a heating rate of 10°C / min, and holding at 135°C for 2 min; the injection port temperature is 180°C; the solution injection amount is 3 μl; and a thermal conductivity detector is at 200°C.
3. 2. The photosensitive resin laminate according to claim 1, wherein the two or more photosensitive resin layers each independently have a thickness of 50 μm to 300 μm.
4. 2. The photosensitive resin laminate according to claim 1, which comprises 2 to 4 photosensitive resin layers.
5. 2. The photosensitive resin laminate according to claim 1, wherein the two or more photosensitive resin layers are each independently a dry film.
6. Two or more photosensitive resin layers are each independently (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, and The photosensitive resin laminate according to claim 1 , further comprising (C) a photopolymerization initiator.
7. 7. The photosensitive resin laminate according to claim 6, wherein the ethylenically unsaturated compound component (B) comprises one or more difunctional acrylate compounds.
8. 8. The photosensitive resin laminate according to claim 7, wherein the amount of the bifunctional acrylate compound is 60% by weight or more based on the weight of the ethylenically unsaturated compound component (B).
9. The photosensitive resin laminate according to any one of claims 1 to 8, and A composite laminate comprising a non-photosensitive resin film on at least one surface of a photosensitive resin laminate.
10. 10. The composite laminate of claim 9, wherein the non-photosensitive resin film is selected from the group consisting of polyethylene terephthalate film, polyolefin film, and composites thereof.
Citation Information
Patent Citations
Photosensitive resin composition, photosensitive element and method for manufacturing photosensitive element
JP2006106287A
Photosensitive permanent resist film and permanent pattern forming method
JP2006285179A
Circuit board and manufacturing method thereof
JP2007165416A
Photosensitive dry film resist and printed wiring board using the same
JP2007310201A
Photosensitive dry film resist, and printed wiring board and method for producing printed wiring board using the same
JP2009048170A